The effect of managerial ownership and capital structure on stock returns with dividend policy as an intervening variable - R. Dian Wirdiansyah; Agus Munandar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The objective of this study is to gather empirical data regarding the impact of management ownership and capital structure on stock returns, with dividend policy acting as an intervening factor. This study employs quantitative methodologies. The study focuses on the consumer products industrial sector listed on the Indonesia Stock Exchange for the period of 2020-2021. A subset of 25 organizations was chosen using the Purposive sampling approach, which adheres to specific criteria. This study demonstrates that the ownership of insiders has an impact on the structure of capital and, consequently, on the policy regarding the distribution of dividends. Stock returns are influenced by managerial ownership and dividend policy, but capital structure does not have an impact on stock returns. Furthermore, the outcome of the Sobel test demonstrates that dividend policy does not have the capability to moderate the impact of managerial ownership and capital structure on stock returns.